2022
DOI: 10.22207/jpam.16.1.08
|View full text |Cite
|
Sign up to set email alerts
|

Corona Discharge Power of Plasma Treatment Influence on the Physicochemical and Microbial Quality of Enoki Mushroom (Flammulina velutipes)

Abstract: Plasma treatment was widely known as an effective technology applied for contact-surface decontamination. Enoki (Flammulina velutipes) was an edible-medicinal mushroom with different phytochemicals and bioactive components beneficial for human health. Enoki mushroom had high respiration rate therefore it was highly perishable after harvesting. Moreover, it was greatly susceptible to microbial contamination but it was not feasible to be decontaminated by normal water washing. It’s urgent to extend shelf-life an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…The golden mushroom has a high respiration rate and is susceptible to spoilage after harvest. Additionally, it is susceptible to microbial contamination and cannot be decontaminated by normal water washing 25 . As such, the application of drying methods to extend the shelf life of F. velutiper and control the microbiological standards has become an urgent priority.…”
Section: Methods For Storing and Preserving F Velutipermentioning
confidence: 99%
See 2 more Smart Citations
“…The golden mushroom has a high respiration rate and is susceptible to spoilage after harvest. Additionally, it is susceptible to microbial contamination and cannot be decontaminated by normal water washing 25 . As such, the application of drying methods to extend the shelf life of F. velutiper and control the microbiological standards has become an urgent priority.…”
Section: Methods For Storing and Preserving F Velutipermentioning
confidence: 99%
“…Plasma is one of four widely used cold atmospheric pressure plasma sources in the food industry 84 . Minh et al 25 . investigated the effect of corona discharge plasma power (control, 120, 150, 180, 210 W) on the physicochemical and microbiological characteristics of F. velutiper stored at room temperature for 10 days.…”
Section: Methods For Storing and Preserving F Velutipermentioning
confidence: 99%
See 1 more Smart Citation
“…It is used in edible mushroom preservation, where it can preserve the color, pH, and texture of mushrooms and reduce weight loss rates 63 . Minh et al 64 . used corona discharge plasma to treat F. velutipes and showed that it could maintain physicochemical indicators such as weight loss, soluble solids, and ascorbic acid in the product, while effectively slowing the total bacterial count.…”
Section: New Processing Techniquesmentioning
confidence: 99%
“…62 It is used in edible mushroom preservation, where it can preserve the color, pH, and texture of mushrooms and reduce weight loss rates. 63 Minh et al 64 used corona discharge plasma to treat F. velutipes and showed that it could maintain physicochemical indicators such as weight loss, soluble solids, and ascorbic acid in the product, while effectively slowing the total bacterial count. Pourbagher et al 65 treated A. bisporus using surface media blocking discharge plasma technology, a method that effectively inhibited enzymatic browning and inactivated Pseudomonas torulosa, extending the storage life of the mushroom.…”
Section: Cold Plasmamentioning
confidence: 99%